“Transparency” of Textbook Activities as Perceived by Chinese Middle School English Teachers With Different Professional Experience - Xu, Hao (Frontiers in Psychology, 2021)
Transparency of textbook activities, i.e., the degree of easiness for teachers’ to process and comprehend them, needs to be researched in terms of both materials design and materials use. This article reports on a study which investigats the impact of teachers’ professional experience and transparency of textbook activities (due to materials design) on teachers’ actual perception of the transparency of materials. The study adopted a mixed-methods design, and collected quantitative data via a five-point scale survey from 115 secondary school teachers as well as interview data from 15 informants. Data analysis reveals that both teachers’ professional experience and transparency of textbook activities impact on the degree of easiness teachers perceived as they understand and interpret the activities for pedagogical purposes. However, discrepancy exists between transparency in materials design and transparency in teachers’ perception. Lack of pedagogical knowledge about the relationship between teaching objectives, steps and assessment and strong existing cognitive schemata developed from the stereotype of processing a more familar set of teaching materials might hamper teachers’ perception of transparency.